IMPROVING LEARNING OUTCOMES AND STUDENT RESPONSES THROUGH PROJECT BASED LEARNING MODEL ON LIGHT AND OPTICAL INSTRUMENTS - Galang Sasmito Aji; Darmadi Darmadi; Rohmawati (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2023)
This study aimed to improve the results and learning responses of class VIII-F students of SMPN 1 Ngasem through the application of the Project Based Learning (PjBL) learning model. The subjects in this study were class VIII-F students of SMPN 1 Ngasem with a total of 21 students. The type of research conducted was Classroom Action Research (PTK) which was conducted in two learning cycles. There are four stages in classroom action research, namely: (1) planning, (2) implementation, (3) observation, and (4) reflection. The data collection technique used in this study was the learning achievement test and student response questionnaires. The results of the study show that applying the project based learning model is quite effective in improving student learning outcomes. Based on the learning outcomes of the cognitive domain on science learning outcomes, it was found that the mastery learning conditions before the action (observation), cycle I, and cycle II showed a percentage of completeness of 28%, 57% and 76%. Besides that, through this learning model, a positive response was obtained from students who obtained an increase in the percentage of responses from cycle I and cycle II, which obtained a percentage of 67.5% which was included in the good criteria, and 83% which was included in the very good criteria. So, it can be concluded that learning science by applying the Project Based Learning (PjBL) model is able to improve the learning outcomes and responses of class VIII students.